Analisis determinan ekspor kayu lapis Indonesia ke Jepang - Wildayanti; Nurjanah, Rahma; Mustika, Candra (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
This study aims to determine and analyze the development of the exchange rate, Japanese GDP, Indonesian plywood production, and exports to Japan and to determine and analyze the effect of the exchange rate, Japanese GDP, and output on Indonesian plywood exports to Japan. The method used is descriptive and quantitative analysis. The analysis tool uses multiple regression with the ordinary least square (OLS) method. The results of this study indicate that the development of the exchange rate, Japanese GDP, and production in the study period tend to fluctuate. The calculations using the Multiple Linear Regression analysis model show that the Japanese GDP variable has a significant negative effect and production has a significant positive impact. In contrast, the exchange rate variable has no significant effect on the volume of Indonesian plywood exports to Japan. Keywords: Exchange rate, Japanese GDP, Production, and volume of Indonesian plywood exports to Japan